Public Finance Policy on Online Loans in Indonesia - Wiyono, Wiyono; Nurmandi, Achmad (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2023)
This study aims to analyze public policy on online loan issues in Indonesia over the last five years’ edition. There were 22,986 complaints from the public regarding online loans until August 2021, so this research chose online loans in Indonesia. To find out, the researchers reviewed 65 news from Indonesian online media related to online loans from the 2016 to 2021 editions. This research used a Qualitative Data Analysis Software approach (QDAS) to study news reviews in Indonesian online media. This research data analysis projection used the Nvivo 12 plus tool with the NCapture feature. The data analysis showed that fintech could only be given material criminal sanctions. Material losses based on complaints must be losses from cases reported by the community—material criminal sanctions for terror and intimidation closely related to public complaints. The research findings showed that the law on fintech was fundamental, and the contents of one of its articles must contain illegal fintech, which can be subject to criminal sanctions without complaint or formal. The government must reform regulations and create new businesses so that a law on the digital financial services sector is formed immediately, also the ratification of the draft personal data protection law to protect citizens. Data protection is significant because it protects victim data often exploited by illegal fintech.